Negotiation Excellence: The practical art of cutting deals - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
In a diverse world of different goals, opinions and agendas, the power to negotiate may be the single-most important determinant of a person or entity's, well, power. Yet, success in negotiations requires a certain finesse that has proven elusive to teach or study. Michael Benoliel, a negotiation specialist at SMU and editor of the recently published book, 'Negotiation Excellence: Successful Deal Making', weighs in on the topic. --------------------------------------------------------------------------------